Spintronics, spin electronics - Monteblanco, Elmer (2013)
Current technology seeks to develop nanoscale devices capable of storing and processing information. These devices would be difficult to make in the area of electronics, which is based on the manipulation of electric charge. However, thanks to advances in experimental and theoretical physics in the field of condensed matter, these devices are already a reality, belonging to the field of what we now call spintronics, which bases its functionality on the control of the electron’s spin, a property that can only be conceived at the quantum level. In this article we review this new perspective, describing giant- and tunneling- magnetoresistance, the spin transfer torque, and their applications such as MRAM memories, nano-oscillators and lateral spin valves.